The ombudsman for children: an analysis of the strengths and weaknesses of the Irish model - Martin, Frank (2004)
The Ombudsman's Office will, compared to other similar offices throughout the world, have a very broad remit in so far as it will be designated with two particular roles, the first of which involves the promotion and welfare of children while the second will centre on the investigation of complaints. To broaden the remit any further would lead to a cross-over into many other areas of work. - Reproduced.
Keywords: Children - Ireland; Ombudsman - Ireland; Ombudsman